2007
DOI: 10.1111/j.1460-9568.2007.05318.x
|View full text |Cite
|
Sign up to set email alerts
|

Doublecortin‐like, a microtubule‐associated protein expressed in radial glia, is crucial for neuronal precursor division and radial process stability

Abstract: During corticogenesis, progenitors divide within the ventricular zone where they rely on radial process extensions, formed by radial glial cell (RG) scaffolds, along which they migrate to the proper layers of the cerebral cortex. Although the microtubule-associated proteins doublecortin (DCX) and doublecortin-like kinase (DCLK) are critically involved in dynamic rearrangement of the cytoskeletal machinery that allow migration, little is known about their role in early corticogenesis. Here we have functionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 51 publications
11
95
1
Order By: Relevance
“…Consistent with previous studies, 25,26 YFP was detected in the nerve bundles of the submucosa and occasionally observed in the gastric mucosa (Supplemental Figure S6). However, although Dclk1 colocalized in the YFP-positive neural cells in the gastric submucosa, we did not observe any copositive cells for Dclk1 and YFP in the glands of either the gastric fundus or antrum (Figure 7).…”
Section: Dclk1-expressing Cells In the Stomachsupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with previous studies, 25,26 YFP was detected in the nerve bundles of the submucosa and occasionally observed in the gastric mucosa (Supplemental Figure S6). However, although Dclk1 colocalized in the YFP-positive neural cells in the gastric submucosa, we did not observe any copositive cells for Dclk1 and YFP in the glands of either the gastric fundus or antrum (Figure 7).…”
Section: Dclk1-expressing Cells In the Stomachsupporting
confidence: 79%
“…The Dclk1 gene is expressed in precursors of neural stem cells. 25,26 Wnt1 is a crucial signaling molecule involved in neural tube formation during embryogenesis and expressed in the mid-hindbrain isthmus area and in neural crest cells. 16 Thus, we performed a lineage tracing study using the Wnt1-specific Cre driver mouse strain.…”
Section: Dclk1-expressing Cells In the Stomachmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene product of Metrnl is a protein akin to meteorin, a secreted protein expressed in undifferentiated neural progenitors (Nishino et al, 2004). Dclk1 encodes a microtubule-associated protein and plays a role in neurogenesis and neuronal migration (Shu et al, 2006;Vreugdenhil et al, 2007). Dlck1 has many alternative splicing variants including Carp (Ania-4) and Dclk1-short (Schenk et al, 2007;Vreugdenhil et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, multiple groups reported the importance of Dclk1 in the developing brain based on its expression in radial glia cells and neuronal precursors. [1][2][3][4][5][6][7] Outside of the nervous system, Dclk1 was initially proposed to mark quiescent gastrointestinal stem cells. 8 Careful lineage tracing studies, however, led to a more elaborate and nuanced understanding of the properties and function of Dclk1C cells in the gastrointestinal tract (see below).…”
Section: Introductionmentioning
confidence: 99%